2016
DOI: 10.1038/srep28165
|View full text |Cite
|
Sign up to set email alerts
|

N-3 long-chain polyunsaturated fatty acids and risk of all-cause mortality among general populations: a meta-analysis

Abstract: Prospective observational studies have shown inconsistent associations of dietary or circulating n-3 long-chain polyunsaturated fatty acids (LCPUFA) with risk of all-cause mortality. A meta-analysis was performed to evaluate the associations. Potentially eligible studies were identified by searching PubMed and EMBASE databases. The summary relative risks (RRs) with 95% confidence intervals (CIs) were calculated using the random-effects model. Eleven prospective studies involving 371 965 participants from gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…n -3 PUFAs can be found in foods like fish, fish oil, marine sources, flaxseed, nuts, and eggs [99]. n -3 PUFAs intake also can boost mood [101], modulate the magnitude of inflammatory responses to stressors [102], and reduce the risks of cardiovascular disease, cancer [103, 104], and all-cause mortality [105]. Insights into mechanisms that may contribute to the beneficial health effects of n -3 PUFAs can be gleaned by reviewing recent work by Kiecolt-Glaser et al [106], showing that n -3 PUFAs supplementation positively impacted cell aging, thereby highlighting how inflammation, oxidative stress, and immune cell aging—which appear to be important mechanisms prior to disease onset—that may be ameliorated through nutritional interventions.…”
Section: Dietary Factors and Nutrition In Breast Cancer Riskmentioning
confidence: 99%
“…n -3 PUFAs can be found in foods like fish, fish oil, marine sources, flaxseed, nuts, and eggs [99]. n -3 PUFAs intake also can boost mood [101], modulate the magnitude of inflammatory responses to stressors [102], and reduce the risks of cardiovascular disease, cancer [103, 104], and all-cause mortality [105]. Insights into mechanisms that may contribute to the beneficial health effects of n -3 PUFAs can be gleaned by reviewing recent work by Kiecolt-Glaser et al [106], showing that n -3 PUFAs supplementation positively impacted cell aging, thereby highlighting how inflammation, oxidative stress, and immune cell aging—which appear to be important mechanisms prior to disease onset—that may be ameliorated through nutritional interventions.…”
Section: Dietary Factors and Nutrition In Breast Cancer Riskmentioning
confidence: 99%
“…The double bond closest to the methyl (ω) end of a fatty acid, usually three or six carbons, differentiates LC‐PUFAs into ω 3 or ω 6 classes, respectively. Evidence suggests consuming LC‐PUFAs in adequate amounts with a balanced ratio among LC‐PUFAs is essential for human physical and mental health (Chen et al ., ), while current diets are often low in ω 3 LC‐PUFAs.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several interesting observational studies that investigated the relationships between dietary or circulating n-3 LCPUFAs and all-cause mortality, and these have recently been assessed by a systematic review and meta-analysis that included 11 prospective observational studies [29]. The studies included 371,965 participants from general populations and considered 31,185 death events.…”
Section: What Do Observational Studies Tell Us About Dha and Ara In Ementioning
confidence: 99%
“…From this analysis, the dose-response indicated that for each 0.3 g/day increment in n-3 LCPUFA intake, there was an associated 6% lower risk of all-cause mortality and for each 1% increment in the proportions of circulating DHA and EPA in total fatty acids in blood there was an associated 21 and 20% decreased risk of all-cause mortality respectively. Moderate to high heterogeneity was observed across the analysis, but the authors concluded that the findings suggest that both dietary and circulating ­LCPUFA are inversely associated with all-cause ­mortality [29]. …”
Section: What Do Observational Studies Tell Us About Dha and Ara In Ementioning
confidence: 99%